Physiological response of culture media-grown barley (Hordeum vulgare L.) to titanium oxide nanoparticles. (19th May 2017) - Kořenková, Lucia; Šebesta, Martin; Urík, Martin; Kolenčík, Marek; Kratošová, Gabriela; Bujdoš, Marek; Vávra, Ivo; Dobročka, Edmund
ABSTRACT: Since the fate of nanoparticles after their release in the environment and their possible transfer in plants and subsequent impacts is still largely unknown, this paper evaluates the potential phytotoxic effects of up to 20% w/w TiO2 nanoparticles ( n TiO2 ) on barley cultivated in hydroponics and agar media. The X-ray diffraction analysis confirmed that n TiO2 powder corresponds to anatase phase. On agar medium only high concentrations of n TiO2 (10% and 20% w/w) induced significant inhibition of shoot growth. However, hydroponics treatment with n TiO2 up to 1000 mg L −1 did not show any adverse effect on the shoot growth. In both experiments, (i) root growth inhibition effects became visible with increasing concentration of n TiO2, (ii) plants treated with n TiO2 showed no change in chlorophyll a and b content, even though the plants absorbed n TiO2, (iii) weight of biomass treated with n TiO2 was not significantly different compared to control. Therefore, we assume that transport of n TiO2 into the aerial parts is limited due to the presence of effective mechanical or physiological barriers in roots. Overall, it appears that early root growth is a relevant indicator of potential effects of n TiO2 exposure. Our results also indicate that synthesized n TiO2 are not significantly toxic to the barley when applied at the concentrations used in this work, even though plants absorb titanium.